Transformational leadership positive influence toward employee engagement through job satisfaction and its effect on improving organizational commitment - Anik Herminingsih (Jurnal Manajemen dan Pemasaran Jasa, 2020)
This study aims to analyze the effect of transformational leadership on Organizational commitment through job satisfaction and employee engagement as mediating variables. Furthermore, as many as 112 nurses are involved as respondents, and the data are gathered with self-rating questionnaire. The Data are analyzed by using structural equation model. The confirmatory factor analysis shows that all questions in the instruments are valid and reliable. The research indicates that transformational leadershippositively and significantly affects on job satisfaction and employees’ engagement, but it does not have a direct effect on organizational commitment. Therefore, it is concluded that transformational leadership has a positive effect on organizational commitment mediated by job satisfaction and employee engagement.